Biochemical Characterization of an FAD-Dependent Monooxygenase, the Ornithine Hydroxylase from Pseudomonas aeruginosa, Suggests a Novel Reaction Mechanism - Meneely, Kathleen M. (2007)
Pyoverdin is the hydroxamate siderophore produced by the opportunistic pathogen Pseudomonas aeruginosa under the iron-limiting conditions of the human host. This siderophore includes derivatives of ornithine in the peptide backbone that serve as iron chelators. PvdA is the ornithine hydroxylase, which performs the first enzymatic step in preparation of these derivatives. PvdA requires both FAD and NADPH for activity, and was found to be a soluble monomer most active at pH 8.0. The enzyme demonstrated Michaelis-Menten kinetics using an NADPH oxidation assay, but a hydroxylation assay indicated substrate inhibition at high ornithine concentration. PvdA is highly specific for both substrate and coenzyme, and lysine was shown to be a non-substrate effector and mixed inhibitor of the enzyme with respect to ornithine. Chloride is a mixed inhibitor of PvdA in relation to ornithine but a competitive inhibitor with respect to NADPH, and a bulky mercurial compound (para-chloromercuribenzoate) is a mixed inhibitor with respect to ornithine. Steady state experiments indicate that PvdA:FAD forms a ternary complex with NADPH and ornithine for catalysis. PvdA in the absence of ornithine shows slow substrate-independent flavin reduction by NADPH. Biochemical comparison of PvdA to para-hydroxybenzoate hydroxylase (PHBH from Pseudomonas fluorescens) and flavin-containing monooxygenases (FMOs from Schizosaccharomyces pombe and hog liver microsomes) leads to the hypothesis that PvdA catalysis proceeds by a novel reaction mechanism.